(untitled) (Revista Interdisciplinar de Marketing, 2016)
Marketing and consumer research is often associated with the methods of natural science applied to experimental and survey data, but there are also strong traditions of interpretive and qualitative work that draw on disciplines such as qualitative sociology, ethnography and anthropology. This paper outlines one such approach, authoethnography, in order to consider its wider adoption in marketing and consumer research. The paper refers to multidisciplinary sources along with autoethnographic studies published in American and European marketing and consumer research journals. It concludes by suggesting that a stronger understanding of autoethnographic research principles could broaden the scope, reach and relevance of marketing and consumer research.